Mycotoxins, antioxidant capacity, physicochemical and sensory quality of specialty coffees from Cajamarca, Peru - Sarasara Akuts, Linder (2026)
Coffee is a globally important crop with significant economic and social relevance, particularly in the Cajamarca region of Peru, which is recognized for the production of high-quality beans. This study aimed to evaluate the occurrence of mycotoxins in three specialty coffee varieties while simultaneously assessing their physical, sensory, and compositional characteristics. A total of 36 parchment coffee samples were randomly collected from two storage facilities located in the provinces of Jaén and San Ignacio. The results revealed the exclusive presence of aflatoxin G₂, with concentrations varying between storage conditions. The Catimor variety exhibited the highest antioxidant activity and total polyphenol content; however, it showed lower physical yield and reduced sensory scores. In contrast, the Bourbon variety displayed a more balanced profile between bean composition and cup quality, producing a beverage with superior physical and sensory attributes and enriched with bioactive compounds associated with potential health benefits. These findings highlight the relevance of varietal selection, post-harvest management, and storage conditions for maintaining coffee quality. Nevertheless, the detection of aflatoxin G₂ indicates persistent food safety concerns, emphasizing the need for stricter monitoring and control measures during harvesting, drying, storage, and handling to mitigate potential health risks.